2003
DOI: 10.1111/j.1745-6584.2003.tb02403.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Heat and Bromide as Ground Water Tracers Near Streams

Abstract: Heat and bromide were compared as tracers for examining stream/ground water exchanges along the middle reaches of the Santa Clara River, California, during a 10-hour surface water sodium bromide injection test. Three cross sections that comprise six shallow (<1 m) piezometers were installed at the upper, middle, and lower sections of a 17 km long study reach, to monitor temperatures and bromide concentrations in the shallow ground water beneath the stream. A heat and ground water transport simulation model and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 21 publications
3
99
0
2
Order By: Relevance
“…Other authors reported values for longitudinal and transverse thermal dispersivity equal to 100 and 10 m, respectively, (Smith and Chapman 1983) or longitudinal thermal dispersivity values in the order of magnitude of 0.01 m to 1 m in case of water exchange between streams and groundwater reservoirs (Niswonger and Prudic 2003). Constantz et al (2003) derived that thermal dispersivity is significantly smaller than solute dispersivity. Bear (1972), Ingebritsen andSanford (1998), andHopmans et al (2002), among others, concluded that effects of thermal dispersion are negligible compared to diffusion and considered α * to be zero.…”
Section: Heat Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors reported values for longitudinal and transverse thermal dispersivity equal to 100 and 10 m, respectively, (Smith and Chapman 1983) or longitudinal thermal dispersivity values in the order of magnitude of 0.01 m to 1 m in case of water exchange between streams and groundwater reservoirs (Niswonger and Prudic 2003). Constantz et al (2003) derived that thermal dispersivity is significantly smaller than solute dispersivity. Bear (1972), Ingebritsen andSanford (1998), andHopmans et al (2002), among others, concluded that effects of thermal dispersion are negligible compared to diffusion and considered α * to be zero.…”
Section: Heat Transportmentioning
confidence: 99%
“…For instance, Bravo et al (2002) involved measurements of surficial temperature in the parameter estimation process of a coupled groundwater and heat flow model of a wetland system in Wisconsin. Constantz et al (2003) made a comparison between heat and bromide as groundwater tracer in the vicinity of streams. Other examples are cited in the paper of Anderson (2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore heat as a tracer at MAR sites has a great potential because it has been used near streams (Lapham 1989;Stonestrom and Constantz 2003;Constantz et al 2003;Anderson 2005). A few recent studies have employed heat as a tracer at spreading basins to determine spatial and temporal variations of infiltration rates (Racz et al 2012;.…”
Section: Intrinsic Heat Tracermentioning
confidence: 99%
“…For semi-arid and arid regions, the water exchange between surface water and groundwater is the critical process of the entire water cycle (Constantz et al, 2003a). Tracers are widely used by hydrologists to indicate the interaction pattern between surface water and groundwater (Banks et al, 1996;Torgersen et al, 2001;Constantz et al, 2003b;Huang et al, 2012). Utilizing geochemical tracers in surface water and groundwater interaction studies bears the disadvantages of uncertainties from the spatial heterogeneity and measurement equipment errors.…”
Section: Introductionmentioning
confidence: 99%